Cultural features of cities communication along the great silk road in the territory Of Kazakhstan (Journal of Philosophy Culture and Political Science, 2016)
This article discusses cultural features of the Great Silk Road communication and the formation of cities in Kazakhstan and neighbouring regions. In particular, the paper focuses on the city of Otrar, a communication space that was described by chroniclers as being “about one day’s journey in all directions”. Otrar was the birth place of philosopher and scientist Al Farabi, also known as the ‘second teacher’ after Aristotle. Al Farabi’s works can be said to tend a bridge between Eastern and Western philosophical and political systems, connecting also a wide range of disciplines. The paper also discusses the project “Revival of the Great Silk Road” which provides an opportunity for Kazakhstan to implement the advantages of its geographical position, aiming at the building of modern infrastructures, the modernization of existing cultural sites along the Silk Road.